Emergence and breakup of a cluster of ordered microparticles during the interaction of thermocapillary and thermogravitational convection; Powder Technology; Vol. 379 - Misyura S. Ya. Sergey Yakovlevich; Egorov R. I. Roman Igorevich; Morozov V. S. Vladimir Sergeevich; Zaitsev A. S. Aleksandr Sergeevich (2021, 2021)
Title screen